Cyclic pamidronate treatment for osteogenesis imperfecta: Report from a Brazilian reference center - Pinheiro, Bruna (Genet Mol Biol, 2019)
Treatment of moderate and severe forms of osteogenesis imperfecta (OI) with cyclic pamidronate at the Reference Center for OI Treatment in Southern Brazil was studied. A retrospective cohort study was conducted from 2002 to 2012. Data were obtained during inpatient (drug infusion) and outpatient care. Clinical data, including the presence of blue sclerae, dentinogenesis imperfecta, history and site of the fractures, biochemical data, including calcium, phosphorus, and alkaline phosphatase levels, were systematically collected. Bone mineral density (BMD) was measured using dual energy X-ray absorptiometry (DXA). Forty-five patients (26 females) were included in the study, and the age of the patients at the time of diagnosis ranged from 1 to 144 months, with a median age (p25-p75) of 38 (5-96) months. Most cases presented OI-4 (51.1%), and the median age of the patients at the start of treatment was 3.3 years (25-75 percentiles: 0.5 - 8.7 years). Twenty-four patients (54.5%) had some adverse events or intercurrences during treatment, and the treatment compliance mean was 92.3% (± 10.7). The treatment with intravenous pamidronate has shown to be safe, well-tolerated, and effective in regard to the improvement of BMD and the reduction of the number of fractures in children and adolescents with OI.